2018
DOI: 10.3390/biom8040133
|View full text |Cite
|
Sign up to set email alerts
|

Add-on Immunoadsorption Shortly-after Optimal Medical Treatment Further Significantly and Persistently Improves Cardiac Function and Symptoms in Recent-Onset Heart Failure—A Single Center Experience

Abstract: Background: Immunoadsorption and intravenous immunoglobulin (IVIG) administration may have beneficial effects in patients with dilated cardiomyopathy with end-stage heart failure. We investigated the effect of immunoadsorption with subsequent IVIG administration on cardiac function and symptoms in patients on optimal medical treatment (OMT) for heart failure (HF) with recent-onset cardiomyopathy during long-term follow-up. Methods: Thirty-five patients with recent-onset of HF symptoms received intensive guidel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…After the immunoadsorption treatment, LVEF improved significantly and LV diameters decreased in the course of LV reverse remodeling. These findings have been described before in some small observational studies [1,2,4,8,9] and immunoadsorption treatment has been added as an aetiology-related therapeutic option in the DCM to the latest position paper of the European Society of Cardiology [41].…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…After the immunoadsorption treatment, LVEF improved significantly and LV diameters decreased in the course of LV reverse remodeling. These findings have been described before in some small observational studies [1,2,4,8,9] and immunoadsorption treatment has been added as an aetiology-related therapeutic option in the DCM to the latest position paper of the European Society of Cardiology [41].…”
Section: Discussionsupporting
confidence: 63%
“…Immunoadsorption and subsequent administration of intravenous immunoglobulin (IVIG) have shown beneficial effects on cardiac function in dilated cardiomyopathy (DCM) and end-stage heart failure (HF) [1,2,3,4,5,6,7,8,9]. DCM is a heterogeneous disease entity associated with genetic predisposition, cardiac infection, and inflammation [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In biopsy‐proven chronic enteroviral or adenoviral and/or Parvovirus B19 positive DCM, an immunomodulatory treatment with interferon beta has been recently shown to reduce viral load and improve functional capacity . Small open‐label controlled, or observational studies suggested that removal of circulating antibodies in DCM by immunoadsorption, followed by IgG substitution, resulted in improvement in cardiac function, symptom relief and increased exercise tolerance . At present, immunoadsorption is considered as an experimental treatment option that requires further evaluation in outcome trials.…”
Section: Heart Failure In Dilated Cardiomyopathymentioning
confidence: 99%